Diversidade de Seirini (Collembola, Arthropleona, Entomobryidae), em áreas úmidas da caatinga - Godeiro, Nerivania Nunes (2013)
The family Entomobryidae is one of the most diverse families of Collembola in Northeast Brazil. Data on its diversity may be considered undervalued due to low collection efforts in the region. In this study, five areas in the Northeast region were sampled, to evaluate the species richness of this family. The study was done in the Serra da Jibóia, Santa Terezinha municipality, Bahia; Serra das Confusões, Caracol municipality, Piauí; Chapada do Araripe, Crato municipality, Ceará; Mata do Pau-Ferro, Areia municipality, Paraíba and Parque Nacional de Ubajara, Ubajara municipality, Ceará, all considered humid areas of Caatinga. Collections were made using pitfall traps and entomological aspirators. All the collected material was screened, mounted on slides, identified and, finally, the descriptions of some of the new species encountered were made. A total of 48 Entomobryidae species belonging to nine genera were recorded and 27 of these were new to science, representing a percentage of 56.25% of the total. A new record for Brazil was identified and several new records were made to the States. Seira was the genus with wider distribution and it was the only one found in all areas and the most representative with the highest number of recorded species (26). This result was expected, because individuals of the genus Seira have a good adaptability to semi-arid environments, a fact that has already been proven in previous research. Seven new species of Seira were described. A dichotomous key to genera and species of Seirini from Brazil was drafted. This work demonstrates the great potential of Entomobryidae and Seirini in the Northeast, despite having been held in very restricted areas, obtained important results for the knowledge of fauna of the group